2019
DOI: 10.5194/acp-2018-1045
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial and temporal variability of snowfall over Greenland from CloudSat observations

Abstract: <p><strong>Abstract.</strong> We use the CloudSat data record 2006–2016 to estimate snowfall over the Greenland Ice Sheet (GrIS). We first evaluate CloudSat snowfall retrievals with respect to remaining ground-clutter issues. Comparing CloudSat observations to the GrIS topography (obtained from airborne altimetry measurements during IceBridge) we find that at the edges of the GrIS spurious high snowfall retrievals caused by ground clutter occasionally aff… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 19 publications
(42 reference statements)
3
16
1
Order By: Relevance
“…Additional uncertainty also arises from any near‐surface precipitation occurring within CloudSat's radar blind zone in the lowest 1,440 m of the atmosphere, where ground interference impacts the quality of CloudSat's retrievals. A recent comparison over Greenland displays similar findings from issues arising as a result of ground clutter over alpine regions influencing CPR retrievals of snowfall in the lowest precipitating bin (Bennartz et al, ). The presence of ground clutter contamination contributing to physically improbable snowfall rates is also clearly visible in the secondary reflectivity maximum (between 20 and 30 dBZ) in Figure a from Kulie and Bennartz (), as well as in the unphysically high near‐surface reflectivities (nearing 30 dBZ) for multiple CloudSat overpasses across Greenland in Figure 7 from the same study.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Additional uncertainty also arises from any near‐surface precipitation occurring within CloudSat's radar blind zone in the lowest 1,440 m of the atmosphere, where ground interference impacts the quality of CloudSat's retrievals. A recent comparison over Greenland displays similar findings from issues arising as a result of ground clutter over alpine regions influencing CPR retrievals of snowfall in the lowest precipitating bin (Bennartz et al, ). The presence of ground clutter contamination contributing to physically improbable snowfall rates is also clearly visible in the secondary reflectivity maximum (between 20 and 30 dBZ) in Figure a from Kulie and Bennartz (), as well as in the unphysically high near‐surface reflectivities (nearing 30 dBZ) for multiple CloudSat overpasses across Greenland in Figure 7 from the same study.…”
Section: Discussionmentioning
confidence: 77%
“…However, we note a general underestimation of approximately 50% in CloudSat snow accumulation throughout December and January across all stations. A contributing factor to the underestimation noted in CloudSat's 2C‐SNOW‐PROFILE snowfall has been previously attributed to the inability of the CPR to capture low cumuliform snowfall which comprise about 36% of global snowfall occurrence, within CloudSat's blind zone in the lowest 1.5 km (Bennartz et al, ; Kulie & Milani, ). The impact of near‐surface snowfall on CloudSat estimate underestimation is further noted in a study by Maahn et al (), which showed (for a similar high‐latitude location in Antarctica) that CloudSat underestimates total annual snowfall by approximately 10% due to shallow cumulus snowfall occurring within the radar blind zone.…”
Section: Validation Of Cloudsat Snowfall Estimates At Stations In Thementioning
confidence: 99%
“…. Two recent studies have used CloudSat's CPR to look at snowfall over the GIS in particular: Lenaerts et al (2019) focused on GIS snowfall frequency and leveraged the satellite observations to evaluate climate model output; and Bennartz et al (2019) used the radar measurements to provide the first in-depth, observationally based snowfall rate estimates of the GIS.…”
mentioning
confidence: 99%
“…by surface return. Contamination is most prevalent in regions of steep, icy topography where the digital elevation map used to determine the surface level does not exactly match conditions at the time of the overpass (Bennartz et al, 2019). Palerme et al (2019) showed that the edges of the GIS are particularly prone to clutter in the R04 version of 2CSP, but the updated elevation map in R05 has reduced the number of contaminated pixels.…”
mentioning
confidence: 99%
“…Several studies have used CloudSat for model evaluation by producing gridded snowfall climatologies (i.e., mean annual snowfall rates) across the Arctic and Antarctica (Behrangi et al, ; Bennartz et al, ; Milani et al, ; Palerme et al, ; Palerme, Claud,et al, ; Palerme, et al, ). These climatologies have coarse spatial scales (e.g., 1 to 2° pixel size) to facilitate direct comparison with global climate models (GCMs).…”
Section: Introductionmentioning
confidence: 99%